The Effect of Financial Knowledge, Financial Attitude, and Personality on Financial Management Behavior in ASN Diskoperindag Gresik Regency - Citra Andriani; Sukaris Sukaris (INNOVATION RESEARCH JOURNAL, 2022)
The background in this study is that the behavior of financial management at ASN Diskoperindag Gresik tends to be less good, which is influenced by several factors, namely financial knowledge, financial attitudes, and personality. This study aims to test the effect of financial knowledge, financial attitudes, and personality on financial management behavior at ASN Diskoperindag, Gresik Regency. This research uses quantitative methods. The population in this study amounted to 75, while the sampling used the Probability Sampling technique using Non Probability sampling. The reason is because the population is below 100, all of them are taken. The sample studied by the researchers was 75 ASN Diskoperindag Gresik Regency. The analysis technique uses instrument test, classical assumption test, and hypothesis test. For test tools using the Statistical Package for the Social Sciences (SPSS). The results of this study indicate that financial knowledge has a positive and significant effect on financial management behavior, financial attitudes have a positive and significant effect on financial management behavior, and personality has a positive and significant effect on financial management behavior.